Narcissism and the Tendency to Use Facebook - Gojković, Vesna; Horvat, Vladimir (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The main problem of this study was to determine whether and to what extent narcissism, as an interpersonal personality trait, may be associated with the use of the social network Facebook. For this purpose, the research was conducted on 133 examinees whose average age was 20 years old; 83 final year students of Zrenjanin grammar school and 50 second year students of the Faculty of Legal and Business Studies in Novi Sad. The basic premise was that the young people, who actively participate in social networks, have significantly higher achievement both in the total score of narcissism and in the marked factors of narcissism. Also, we thought that gender, age and educational level are variables that significantly differentiate young people who are more prone to virtual exposure from the young people who are not. For the assessment of narcissism, the NPI-40 questionnaire was used (Pinsky & Young, 1988), which measures subclinical narcissism – operationalised by the total score and already assumes the structure of seven factors (authority, self-sufficiency, superiority, exhibitionism, greed, vanity, entitlement). For the measurement of demographic variables and variables of using Facebook, we used a specially made questionnaire. Correlation between variables was tested using Pearson's correlation method, and to determine the significance of differences for independent samples it was used t-test or ANOVA, depending on the applicability of one of these two tests on certain variables. The results have shown that there is a significant positive correlation between the use of Facebook and total narcissism. The narcissistic self consists of self-sufficiency, exhibitionism and vanity. Also, it was determined that the superiority factor is significantly correlated with the number of photos that users have on Facebook and that makes significant differences between male and female examinees. Finally, it was found that high school students are much more narcissistic than college students are, and that this difference can be defined primarily by the factor of preferential right.